IDNLearn.com provides a reliable platform for finding accurate and timely answers. Our platform offers reliable and comprehensive answers to help you make informed decisions quickly and easily.
Sagot :
Answer:
Answer is the first one, i know tricks boy
Step-by-step explanation:
The given function f(x) is equivalent to (x-8((x-3).
We have given function is,
[tex]f(x)=x^2-5x-24[/tex]
We have to find the equivalent expression of the f(x).
What is the ac method?
The ac Method is a method of factoring trinomial in the form
[tex]ax^{2} + bx + c=0[/tex].....(1)
The ac method of factoring is basically a method to that you can eventually factor the trinomial using grouping. In order to split the middle term (in this case bx), we will need to find the factors that make up the product of the coefficient a and c.
Compare the the given function with equation 1 and find the value of a,b,c
[tex]f(x)=x^2-5x-24[/tex]
by given polynomial
a=1,b=-5 and C=-24
By using AC method
ac=(1)(-24)
ac=-24=-8(3)
b=-8+3=-5
[tex]=x^2-8x-3x-24\\\\=x(x-8)+3(x-8)\\\\=(x-8)(x+3)[/tex]
Therefore,
The given function f(x) is equivalent to (x-8((x-3).
To learn more about the equivalent expression visit:
https://brainly.com/question/24734894
We are delighted to have you as part of our community. Keep asking, answering, and sharing your insights. Together, we can create a valuable knowledge resource. Thank you for choosing IDNLearn.com. We’re here to provide reliable answers, so please visit us again for more solutions.